Stream Barb Influenced on Straight Channel Bed Configuration: A Numerical Simulation (Journal of Environmental Science and Natural Resources, 2015)
The focus of this study is to observe the influence of barb on channel bed configuration by using iRIC-Nays2D, a multi-dimensional computational model for river flow and riverbed variation analysis solver package. The two-dimensional (2D) numerical simulation is represent the effects the pre-existing condition (i.e. before construction of barb) and in the presence of the barb installed on sidewall of the channel. The average flow depth, and discharge were used as 0.044 m and 0.028 m3/s, respectively. The numerical simulation reproduced the features of barb with time at upward side and creates scour holes at the leeward side of the structure. The simulation results confirmed that the vicinity of the barb head achieved a substantial reduction in scour, increase stream-wise velocity and sediment deposition at near bank. Bars were formed along the bank-line at the upstream portion of the structures. On the other hand, at the downstream side near the barb head scour occurs due to hydraulic jump and turbulence flow mixing.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22110 J. Environ. Sci. & Natural Resources, 6(2): 139-147 2013